Quercetin Increases Hepatic Homocysteine Remethylation and Transsulfuration in Rats Fed a Methionine-Enriched Diet. (19th October 2015) - Meng, Bin; Gao, Weina; Wei, Jingyu; Pu, Lingling; Tang, Zhenchuang; Guo, Changjiang
Abstract : This study was aimed at investigating the effects of quercetin on mRNA expression and activity of critical enzymes in homocysteine metabolism in rats fed a methionine-enriched diet. Rats were fed for 6 weeks the following diets, that is, control, 0.5% quercetin, 1.0% methionine, and 1.0% methionine plus 0.5% quercetin diets. Serum homocysteine was significantly increased after methionine treatment and decreased after the addition of quercetin. The mRNA expression of methionine synthase was significantly increased after methionine or methionine plus quercetin supplementation, while its enzymatic activity was significantly increased after methionine plus quercetin supplementation. The mRNA expression and enzymatic activity of cystathionine β -synthase and cystathionine γ -lyase were upregulated after quercetin, methionine, or quercetin plus methionine treatment and a more significant increase was observed for hepatic cystathionine β -synthase in the methionine plus quercetin treated rats, suggesting an interaction between methionine and quercetin. Meanwhile, hepatic ratio of S-adenosylmethionine to S-adenosylhomocysteine was significantly decreased in response to methionine supplementation and normalized after the addition of quercetin. It is concluded that quercetin reduces serum homocysteine by increasing remethylation and transsulfuration of homocysteine in rats exposed to a methionine-enriched diet.